Advances in tissue engineering of peripheral nerve and tissue innervation – a systematic review - Jayson Sueters; Rowan van Heiningen; Ralph de Vries; Zeliha Guler; Judith Huirne; Theo Smit (Journal of Tissue Engineering)
Although various options are available to treat injured organs and peripheral nerves, none is without limitations. Auto- and allografts are the first choice of treatment, but tissue survival or functionality is not guaranteed due to often limited vascular and neural networks. In response, tissue-engineered solutions have been developed, yet clinical translations is rare. In this study, a systematic review was performed on tissue-engineered advancements for peripheral nerves and tissues, to aid future developments in bridging the gap toward the clinic by identifying high-potential solutions and unexplored areas. A systematic search was performed in PubMed, Embase, Web of Science, and Scopus until November 9, 2023. Search terms involved “tissue engineering,” “guided,” “tissue scaffold,” and “tissue graft,” together with “innervation” and “reinnervation.” Original in vivo or in vitro studies meeting the inclusion criteria (tissue-engineered peripheral nerve/innervation of tissue) and no exclusion criteria (no full text available; written in foreign language; nonoriginal article; tissue-engineering of central nervous system; publication before 2012; insufficient study quality or reproducibility) were assessed. A total of 68 out of 3626 original studies were included. Data extraction was based on disease model, cell origin and host species, biomaterial nature and composition, and external stimuli of biological, chemical or physical origin. Although tissue engineering is still in its infancy, explored innervation strategies of today were highlighted with respect to biomaterials, cell types, and external stimuli. The findings emphasize that natural biomaterials, pre-seeding with autologous cell sources, and solutions for reproductive organs are beneficial for future research. Natural biomaterials possess important cues required for cell-material interaction and closely resemble native tissue in terms of biomechanical, geometrical and chemical composition. Autologous cells induce biomaterial functionalization. As these solutions pose no risk of immunorejection and have demonstrated good outcomes, they are most likely to fulfill the clinical demands.